Mortgage Rights as a Guarantee of Legal Protection for Creditors in Financing According to Thomas Hobbes's Theory of Justice - Marbun, Bachtiar; Santoso, Budi; ., Yunanto (Journal of Ecohumanism, 2024)
This study discusses the right of dependency as a guarantee of legal protection for creditors in financing based on the theory of justice from Thomas Hobbes. The right of dependents, as a legal instrument that gives creditors priority rights to repay debts through objects used as collateral, has an important role in maintaining a balance of interests between creditors and debtors. In the context of Hobbes' theory of justice, security and legal certainty are fundamental aspects that need to be maintained to avoid conflicts and ensure a stable social order. This article outlines how Hobbes' concept of justice, which emphasizes the need for the state to maintain order through the rule of law, is relevant to the regulation of dependent rights in the financing system. The right of dependency provides legal certainty to creditors, which can be considered as part of the mechanism to achieve distributive justice in society. In the end, this article concludes that the right of dependency plays a role as a form of legal protection that is fair to creditors, in line with Hobbes's concept of justice which prioritizes security and certainty in social life.